A literature review of preventable hospital readmissions: Preceding the Readmissions Reduction Act. Issue 4 (1st October 2016) - Wan, Hong; Zhang, Lingsong; Witz, Steven; Musselman, Kenneth J.; Yi, Fang; Mullen, Cody J.; Benneyan, James C.; Zayas-Castro, Jose L.; Rico, Florentino; Cure, Laila N.; Martinez, Diego A.
ABSTRACT: Preventable readmissions are a large and growing concern throughout healthcare in the United States, representing as many as 20% of all hospitalizations (30-day post-discharge) and an estimated $17 to $26 billion in unnecessary costs annually. National quality initiatives and Medicare reimbursement financial incentives have stimulated significant efforts by healthcare organizations to reduce readmissions via a number of approaches and interventions. Given the severity and complexity of this problem, this article explores the literature describing descriptive and predictive readmission studies as well as proposed interventions that used a systems engineering approach before the 2011 Medicare program to stimulate reduction of readmissions. A total of 112 publications from 1988 to 2011 were identified and grouped into three general categories: descriptive analyses, intervention studies, and predictive analyses. While a significant amount of work has been conducted in each of these areas, very few systems engineering, industrial engineering, and operations research studies have focused directly on the hospital readmission issue. This article, therefore, concludes with a discussion of potential areas in which industrial engineers could make meaningful contributions to this significant issue.